Islam Nusantara antara Ortodoksi dan Heterodoksi - Akhiyat Akhiyat (IAIN Ponorogo, 2017)
Abstract: Religious style of Indonesia or Islam Nusantara has its own peculiarities. The form that can be found from the different shades of Islamic Archipelago with other countries in the Middle East, especially the Islamic origins of Saudi Arabia, namely in terms of uniqueness of the treasures of the experience and the practice of the Indonesian people as their adherents. It can be said that Islam Nusantara is Islam as moral and moral teachings for its adherents, and not Islam as